Cryptocurrency Digital Assets: Evidence of the Emergence of Cryptocurrency Securities Markets as an Investment Asset Class, 2018-2023 - Miller, Mitchell; Prondzinski, Dale (Journal of Accounting and Finance, 2023)
This study seeks to understand the value of digital assets as investments. The study compared the returns of the FAANG stocks and the S&P 500 TR Index to Bitcoin and the CRIX index. The results found no significant difference between the returns of the FANG stocks and Bitcoin on a risk-adjusted basis. However, the study found a significant difference between the S&P 500 TR Index as compared to Bitcoin and the CRIX index on a risk-adjusted basis. The period of the study, 2018-2023, reflects the relevant time band measured by the number of published studies and academic articles. The authors conclude that while Bitcoin may be an investment of choice for a risk-seeking investment style, better assets of choice exist for a risk-averse investor building a diversified portfolio.